COVID-19 testing in outbreak-free care homes: what are the public health benefits?. (May 2021) - Green, R.; Tulloch, J.S.P.; Tunnah, C.; Coffey, E.; Lawrenson, K.; Fox, A.; Mason, J.; Barnett, R.; Constantine, A.; Shepherd, W.; Ashton, M.; Beadsworth, M.B.J.; et al.
SUMMARY: Background: COVID-19 care home outbreaks represent a significant proportion of COVID-19 morbidity and mortality in the UK. National testing initially focused on symptomatic care home residents, before extending to asymptomatic cohorts. Aim: The aim was to describe the epidemiology and transmission of COVID-19 in outbreak free care homes. Methods: A two-point prevalence survey of COVID-19, in 34 Liverpool care homes, was performed in April and May 2020. Changes in prevalence were analysed. Associations between care home characteristics, reported infection, prevention and control interventions, and COVID-19 status were described and analysed. Findings: No resident developed COVID-19 symptoms during the study. There was no significant difference between: the number of care homes containing at least one test positive resident between the first (17.6%, 95% confidence interval (CI) 6.8–34.5) and second round (14.7%, 95% CI 5.0–31.1) of testing (p>0.99); and the number of residents testing positive between the first (2.1%, 95% CI 1.2–3.4) and second round (1.0%, 95% CI 0.5–2.1) of testing ( P =0.11). Care homes providing nursing care (risk ratio (RR) 7.99, 95% CI 1.1–57.3) and employing agency staff (RR 8.4, 95% CI 1.2–60.8) were more likely to contain test positive residents. Closing residents shared space was not associated with residents testing positive (RR 2.63, 95% CI 0.4–18.5). Conclusions: Asymptomatic COVID-19 care homes showed no evidence of disease transmission or development of outbreaks; suggesting that current infection prevention and control measures are effective in preventing transmission. Repeat testing at two to three weeks had limited or no public health benefits over regular daily monitoring of staff and residents for symptoms. These results should inform policies calling for regular testing of asymptomatic residents.